2021
DOI: 10.3390/antiox10020184
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Alleviates Hypoxia-Induced Apoptosis of Granulosa Cells by Reducing ROS and Activating MTNR1B–PKA–Caspase8/9 Pathway

Abstract: In mammalian ovaries, the avascular environment within follicular cavity is supposed to cause hypoxic status in granulosa cells (GCs), leading to apoptotic cell death accompanied by cumulative reactive oxygen species (ROS) production. Melatonin (N-acetyl-5-methoxytryptamine, MT), a broad-spectrum antioxidant that exists in porcine follicle fluid, was suggested to maintain GCs survival under stress conditions. In this study, using the established hypoxic model (1% O2) of cultured porcine GCs, we explored the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Consistent with these data, previous studies reported that EP4 receptor blockade hindered proliferation and induced apoptosis in cervical cancer cells via the EP4-PKA-CREB pathway. Moreover, reduced PKA induced apoptosis through Bcl-2/Bax-induced apoptosis [23] and activation of the caspase-8/9/11 pathway and pyroptosis [24,25]. The PKA inhibitor blocked PGE2 through EP2-and EP4-induced apoptosis, indicating that the PKA pathway is mainly responsible for PGE2-mediated inhibition of apoptosis [26].…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with these data, previous studies reported that EP4 receptor blockade hindered proliferation and induced apoptosis in cervical cancer cells via the EP4-PKA-CREB pathway. Moreover, reduced PKA induced apoptosis through Bcl-2/Bax-induced apoptosis [23] and activation of the caspase-8/9/11 pathway and pyroptosis [24,25]. The PKA inhibitor blocked PGE2 through EP2-and EP4-induced apoptosis, indicating that the PKA pathway is mainly responsible for PGE2-mediated inhibition of apoptosis [26].…”
Section: Discussionmentioning
confidence: 95%
“…ROS was mainly brought forth through the electron transfer chain and the ROS-detoxifying enzyme pathway. Our previous study demonstrated that hypoxia induced GC apoptosis through ROS. ,, In the present study, we show that SFN supplemented under hypoxic exposure can relieve GC apoptosis by decreasing the level of ROS. Further studies revealed that SFN could increase the expression of NFE2L2-guided antioxidant enzymes such as NQO1, HO-1, SOD1, and SOD2.…”
Section: Discussionmentioning
confidence: 99%
“…After 36 h, porcine GCs were washed with PBS two times and treated with different SFN concentrations (1, 5, and10 μM) or inhibitors. With GCs being cultured in a hypoxic environment, we cultured the cells under hypoxic conditions according to the previous method (1% O 2 , 5% CO 2 , and balanced N 2 ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of endogenous carbon monoxide (CO) in cells comes from the degradation of heme, which is caused by the up-regulation of heme oxygenase-1 (HO-1). HO-1 expression is induced by various stimuli, 1 including reactive oxygen species (ROS), 2 hypoxia, 3 inflammation, viral infection, and stress. Moreover, HO-1 typically catalyzes the degradation of heme into bilirubin, free iron and CO. 4,5 Bilirubin is considered to have an antioxidant effect; 6,7 free iron is usually stored in ferritin, thereby limiting its ability to participate in the Fenton reaction to produce cytotoxic free radicals; 8 CO restrains apoptosis by taking part in the activation of mitogen-activated protein kinase (MAPK) pathways.…”
Section: Introductionmentioning
confidence: 99%